Reclamation of Post Coal Mining Using Hydroseeding Involving Seeds of Some Local Papilionaceae - Rufaidah Nur Baiti; Endang Arisoesilaningsih (University of Brawijaya, 2015)
This study aimed to determine germination rate, growth and morphological adaptation of root, shoot and leaves of some local Papilionaceae seeds sown in a post coal mining from the South Kalimantan using hydroseeding technique. Species used in this study were Desmodium triflorum (L.) DC, Indigofera spicata Forssk, Alysicarpus ovalifolius (Schumach.) J. Léonard, Crotalaria pallida Aiton, Cajanus cajan (L.) Millsp. dan Sesbania grandiflora (L.) Pers. Twenty seeds of each species were mixed with mulches became hydroseeding, sown in the surface of the tailings from South Kalimantan and each treatment was repeated four times. The media were watered periodically to maintain soil field capacity. Seeds germination rate, plant length, leaves number and coverage were observed twice per week. Plants were harvested 37 days after sown (das) to determine root length and nodules number. The results showed that the beans of D. triflorum, I. spicata, C. pallida and S. grandiflora succesfully germinated and grew in the media. Otherwise the beans of A. ovalifolius and C. cajan failed to germinate. Four germinated species grew variably depend on their specific life form. These Papilionaceae adapted well to the selected medium and showed an intensive root penetration to the tailing layer. Besides D. triflorum, I. spicata and C. pallida were capable to produce some nodules. Keyword : Adaptation, post coal mining, Papilionaceae, revegetation